Placing HIV-positive mothers at the centre of planning for orphans and vulnerable children: a case study of South Africa - Norman, Amy; Kadiyala, Suneetha; Chopra, Mickey (International Food Policy Research Institute, 2006)
Worldwide, more than 14 million children have lost a parent to HIV/AIDS. In South Africa, the current epicentre of the epidemic, it is estimated that by 2010, 16% of children will be orphaned by AIDS. The implication of the term “AIDS orphan” has been that parents with AIDS have no plan in place to provide for the care of their children in the event of their deaths. In the majority of policy discourse, women are not seen as agents in the process of preparing their children and future caregivers, or of planning for the future. Effective responses to the challenge of AIDS-induced orphanhood require an understanding of the challenges HIV-positive women face in mothering, as well as the dynamics and strategies used in planning for the future of their children. The inclusion of mothers before the death of a parent is necessary so as to privilege a thus far underutilized resource. The aim of this paper is to present the results of a study that examined the experiences of women undergoing shocks related to the impact of HIV/AIDS in two South Africa communities- Paarl and Umzimkhulu. A total of 25 HIV/AIDS-affected people from 18 households were interviewed, as well as ten key informants. This paper highlights the challenge of maternal disclosure in the African context, the planning for future caregiving, the financial constraints mothers face, and the opportunity undertaken by women to foster future resistance and resilience in their children.